Pengaruh Akuntabilitas dan Transparansi Terhadap Pengelolaan Dana Bantuan Operasional Kesehatan (BOK) pada Puskesmas Sukajadi Kecamatan Talang Kelapa Kabupaten Banyuasin - Yulianti Yulianti; Muhammad Titan Terzaqi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the effect of accountability and transparency on the management of health operational assistance funds (BOK). This research uses quantitative methods. The population in tgis study were all employees of the Sukajadi Health Center with a total of 91 respndents. Sampling using saturated sampling. The analysis technique used is multiple linear regression analysis using the software application program statistical program of social science (SPSS) version 26. The results of this study indicate that accountability has a positive and significant influence on the management of health operational assistance funds (BOK), and transparency has a positive and significant influence on the management of health operasional assistance funds (BOK).